Imaginary Companions, Inner Speech, and Auditory Verbal Hallucinations: What Are the Relations? - Fernyhough, Charles; Watson, Ashley; Bernini, Marco; Moseley, Peter; Alderson-Day, Ben (Frontiers in Psychology, 2019)
Interacting with imaginary companions (ICs) is now considered a natural part of childhood for many children, and has been associated with a range of positive developmental outcomes. Recent research has explored how the phenomenon of ICs in childhood and adulthood relates to the more unusual experience of hearing voices (or auditory verbal hallucinations; AVH). Specifically, parallels have been drawn between the varied phenomenology of the two kinds of experience, including the issues of quasi-perceptual vividness and autonomy/control. One line of research has explored how ICs might arise through the internalization of linguistically-mediated social exchanges to form dialogic inner speech. We present data from two studies on the relation between ICs in childhood and adulthood and the experience of inner speech. In the first, a large community sample of adults (N = 1472) completed online the new Varieties of Inner Speech–Revised (VISQ-R) questionnaire (Alderson-Day et al., 2018) on the phenomenology of inner speech, in addition to providing data on ICs and AVH. The results showed differences in inner speech phenomenology in individuals with a history of ICs, with higher scores on the Dialogic, Evaluative, and Other Voices subscales of the VISQ-R. In the second study, a smaller community sample of adults (N = 48) completed an auditory signal detection task as well as providing data on ICs and AVH. In addition to scoring higher on AVH proneness, individuals with a history of ICs showed reduced sensitivity to detecting speech in white noise as well as a bias towards detecting it. The latter finding mirrored a pattern previously found in both clinical and non-clinical individuals with AVH. These findings are consistent with the view that ICs represent a hallucination-like experience in childhood and adulthood which shows meaningful developmental relations with the experience of inner speech.